Extensive Bowen's disease of the face - combined therapy - Paweł Piłat; Adam Borzęcki; Dorota Krasowska (Termedia Publishing House, 2014)
Introduction. The most commonly diagnosed cancer group in humans is cancers of the skin. One pre‑invasive form of squamous cell carcinoma is Bowen's disease. It manifests in the form of single or multiple lesions, which may be located on the skin of any part of the body. Most often it appears in the form of a well-demarcated, oval patch covered with a small crust. Risk factors are immunosuppression, exposure to arsenic, HPV viruses, solar radiation and X-rays. Objective. Presentation of a case of extensive Bowen's disease, in which combined therapy methods had to be used. Case report. In this paper we present a case of extensive Bowen's disease of the face in an 86-year-old female patient. Due to the difficult location and a large lesion, the combined therapy was used: CO 2 laser, photodynamic therapy and imiquimod. Satisfactory results were achieved. Conclusions . In extensive Bowen's disease in order to remove it and achieve a satisfactory cosmetic effect, combined therapy may be necessary.